Nitrogen requirement of single hybrid maize (Zea mays) - wheat (Triticum aestivum) system under rainfed conditions - PARMAR, D K; SHARMA, VINOD (The Indian Journal of Agricultural Sciences, 2014)
A field experimentwas conducted during kharif 1997 at Bajaura to work out nitrogen requirement of single hybrid maize (Zea mays L.) grown under rainfed conditions. The grain and stover yield of maize increased significantly up to 120 kg /ha of N applied. Farmyard manure at 15 tonnes/ha improved maize productivity to a considerable extent, However, wheat (Triticum aestivum L. emend. Fiori & Paol.) grain and straw yield increased significantly up to 90 kg/ha of N applied. The response of wheat crop to farmyard manure was similar as obtained in maize. The total uptake of N by maize and wheat crops increased with increasing level of nitrogen and farmyard manure but it had no effect on P and K uptake. The addition of farmyard manure @ 20 tonnes/ha improved total uptake of all the nutrients. The status of available N in soil improved due to nitrogen fertilization but P and K did not. The availability of these nutrients further increased with farmyard manure application. Application of 120 kg N/ha + 15 tonnes farmyardmanure/ha was found best treatment for hybrid maize grown under rainfed conditions.